The Cytoplasmic Tail of Influenza A Virus Hemagglutinin and Membrane Lipid Composition Change the Mode of M1 Protein Association with the Lipid Bilayer - Larisa V. Kordyukova; Petr V. Konarev; Nataliya V. Fedorova; Eleonora V. Shtykova; Alexander L. Ksenofontov; Nikita A. Loshkarev; Lubov A. Dadinova; Tatyana A. Timofeeva; Sergei S. Abramchuk; Andrei V. Moiseenko; Lyudmila A. Baratova; Dmitri I. Svergun; et al. (Membranes, 2021)
Influenza A virus envelope contains lipid molecules of the host cell and three integral viral proteins: major hemagglutinin, neuraminidase, and minor M2 protein. Membrane-associated M1 matrix protein is thought to interact with the lipid bilayer and cytoplasmic domains of integral viral proteins to form infectious virus progeny. We used small-angle X-ray scattering (SAXS) and complementary techniques to analyze the interactions of different components of the viral envelope with M1 matrix protein. Small unilamellar liposomes composed of various mixtures of synthetic or “native” lipids extracted from Influenza A/Puerto Rico/8/34 (H1N1) virions as well as proteoliposomes built from the viral lipids and anchored peptides of integral viral proteins (mainly, hemagglutinin) were incubated with isolated M1 and measured using SAXS. The results imply that M1 interaction with phosphatidylserine leads to condensation of the lipid in the protein-contacting monolayer, thus resulting in formation of lipid tubules. This effect vanishes in the presence of the liquid-ordered (raft-forming) constituents (sphingomyelin and cholesterol) regardless of their proportion in the lipid bilayer. We also detected a specific role of the hemagglutinin anchoring peptides in ordering of viral lipid membrane into the raft-like one. These peptides stimulate the oligomerization of M1 on the membrane to form a viral scaffold for subsequent budding of the virion from the plasma membrane of the infected cell.